New insights into nanostructure and geochemistry of bioapatite in REE-rich deep-sea sediments: LA-ICP-MS, TEM, and Z-contrast imaging studies - Liao, Jianlin; Sun, Xiaoming; Li, Dengfeng; Sa, Rina; Lu, Yang; Lin, Zhiyong; Xu, Li; Zhan, Runze; Pan, Yuguan; Xu, Huifang (Chemical geology, 2019)
Rare earth elements (REE) and yttrium (Y), termed as REY, are recently found to be extremely enriched in some pelagic sediments, which could be an important resource for REY in the future. However, their enrichment mechanism remains controversial. Because biogenetic apatite is one of the most important REY carriers in REY-rich deep-sea sediment, it is critical to identify its mineralogical and geochemical characteristics by using combined methods of in situ chemical analysis and atomic resolution chemical imaging. Scanning electron microscope and transmission electron microscopy studies reveal that bioapatite fossils mainly consist of aligned hydroxyapatite nano-plates. Laser ablation-inductively coupled plasma-mass spectrometry analyses show that the REY are not uniformly distributed within the studied bioapatite fossils. Concentration profiles from the measurements and modeling analyses indicate that the major REY should be incorporated into the bioapatite fossil from seawater as well as the pore water during the early stage of diagenesis. Z-contrast imaging results reveal the following two possible coupled substitutions in the apatite: REE3+ + Na+ ↔ 2Ca2+ and/or REE3+ + Si4+ ↔ Ca2+ + P5+, which is distinguished from those ion-absorption-type REE deposits on land. Our study indicates that bioapatite fossils are prone to undergo alteration during diagenesis, and thus cautious examination should be taken when applying REE signal of bioapatite as a proxy for palaeo-ocean environmental reconstruction. [Display omitted] •Z-contrast was used to image substituted REY of bioapatite in atomic resolution.•The extraction of REY in the REY-rich deep-sea sediment needs strong acid.•Bioapatite obtains REE from seawater and/or pore water during early diagenesis.•Histology controls the REE in-diffusion pathway within bioapatite fossils.•Cautious examination is required for using REE signals in bioapatite for palaeoceanographic study.